Beban Kerja Perawat Berhubungan Dengan Kepatuhan Pendokumentasian Asuhan Keperawatan Di IGD RSUD Kota Bogor Tahun 2022: Nurse Workload Related to Compliance with Nursing Care Documentation in the Bogor City Hospital Emergency Room in 2022 - Sunarti, Dwi (Dohara POAJ, 2022)
Introduction: Based on the data obtained from January to May 2022 in the Bogor City Hospital Emergency Room, it was found that the documentation of nursing care was not optimal. 7 Emergency Room nurses said that the workload of nurses was quite heavy with countless patient visits with various criteria. Incomplete documentation of nursing care will lead to a decrease in the quality of nursing services and the occurrence of a problem that has the potential to become a legal case for nursing staff. Therefore, it is necessary to increase knowledge regarding the completeness of proper documentation and motivation from leaders and management so that nurses can complete the documentation of nursing care optimally. Methods: This study uses a cross-sectional descriptive quantitative method, with the type of correlation. The samples taken were 42 respondents. The instruments used were the workload questionnaire from Nursalam and the Hospital Nursing Care Standards (SAK) observation sheet. The dependent and independent variables in this study were Compliance with nursing care documentation and nurses’ workload. Results: The age distribution where nurses were mostly early adults with 33 people (78,6%), and the gender of most of them was 29 people (69%), The distribution of nurses' workload is almost entirely moderate, namely 35 people (83,3%) while the distribution of documentation compliance level is mostly obedient, which is 24 people (57,1%). Correlation Test Results p-value was obtained at 0,031 (< 0,05). Discussion: There is a significant relationship between the workload of nurses and the compliance of nurses' documentation in Bogor City Hospital Emergency Room in 2022.